Pengaruh Manajemen Modal Kerja Terhadap Kinerja Keuangan Perusahaan Manufaktur di Indeks Saham Syariah - Khoirun Nisa Nurul Muslimah; Mochamad Edman Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to determine the effect of Working Capital Management as measured by the variables APP, ITO, ACP and CCC on the Financial Performance of Manufacturing Companies as measured by the variable ROA, ROE and EPS listed on the Sharia Stock Index for the 2015-2019 period. The population in this study uses a purposive sampling method with secondary data obtained from the annual financial statements of manufacturing companies registered at ISSI for the 2015-2019 period. This research uses descriptive analysis and path analysis using the WarpPLS 7.0 analysis tool. From this study, the results obtained that APP has a significant positive effect on ROA, ROE, and EPS. ITO has no significant effect on ROA. ITO has a significant positive effect on ROE and EPS. ACP has a significant positive effect on ROA, ROE, and EPS. CCC has no significant effect on ROA, ROE, and EPS. After a comparison between APP and ACP, it is known that in reality there are still operational activities of the company that are not in accordance with the applicable sharia provisions.